رؤية استراتيجية لمشروع الضبط الببليوجرافي الوطني في دولة الكويت - الحمود، نهلاء داود سلمان (جامعة الكويت - مجلس النشر العلمي, 2011)
تسعى الدراسة إلى وضع إستراتيجية لمشروع الضبط الببليوجرافي الوطني، معتمدة على تحليل واقع المكتبات في دولة الكويت، من حيث حجم المجموعات والعاملين في هذه المكتبات والخدمات الببليوجرافية التي تقدم للمستفيدين ومحاولات التعاون بينها. \ \ وللحصول على تلك المعلومات، تم توزيع استبانة وإجراء مقابلة مع العاملين و المسؤولين في المكتبات، للحصول على البيانات اللازمة وتحليلها، ومن ثم الخروج بتصور واضح عن الخدمات والتعاون بينها، لتساعد على وضع إستراتيجية للضبط الببليوجرافي. \ \ أظهرت نتائج تحليل البيانات، أن هناك غياباً في إيجاد خطة وطنية لحصر الإنتاج الفكري الوطني وحفظ التراث بسبب الاختلاف في النظم وقلة العاملين المتخصصين وضعف دور المكتبة الوطنية. لذا فالدراسة سوف تقترح إستراتيجية للضبط الببليوجرافي. The study aims to formulate a strategy for a national biblio¬graphic control program based on the analysis of the current status of libraries in Kuwait; in terms to the size of publications, staff at libraries, bibliographic services provided to the end user, and areas of mutual cooperation. The required data and information were collected through a questionnaire and structured interviews with workers and officials at the libraries. The results were analyzed in order to obtain a clear vision regarding the services and coordination between activities. This will enable the process of formulating a national bibliographic control program. Data analysis showed clear absence of a national plan to quantify the output of national intellectual literature and preserving national heritage. This was mainly due to system incompatibilities, limited number of specialized personnel, and the functioning role of the National Library. Therefore, the study provided a strategy towards a national bibliographic control program.
Keywords: المكتبات العامة -- الكويت -- المكتبات الوطنية -- الانتاج الفكري -- الببليوجرافيات الوطنية -- الضبط الببليوجرافي -- مراكز المعلومات -- خدمات المعلومات -- شبكات المعلومات -- الحاسبات الإلكترونية